2023
DOI: 10.20961/stjssa.v20i1.63877
|View full text |Cite
|
Sign up to set email alerts
|

The effect of beneficial microorganism as biofertilizer application in hydroponic-grown tomato

Abstract: <p>The use of N<sub>2</sub>-fixing bacteria and growth hormone-producing rhizobacteria delivers nitrogen, enhances nutrients absorption by plants, and reduces the usage of inorganic fertilizers. Implementing biofertilizer in the hydroponic system as a means to reduce application of synthetic nutrient is recently in interest due to economic, food safety, and sustainability factors. This study determines the effects of biofertilizer dose on tomato yields in the hydroponics system. A randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…A higher population of N-fixing bacteria indicates elevated biochemical activity and an improved soil quality. Consistent with other findings, research has reported that biofertilizer treatments have a positive impact on the population of microorganisms in the rhizosphere, leading to an increase in the population of N-fixing bacteria [50,51].…”
Section: Discussionsupporting
confidence: 87%
“…A higher population of N-fixing bacteria indicates elevated biochemical activity and an improved soil quality. Consistent with other findings, research has reported that biofertilizer treatments have a positive impact on the population of microorganisms in the rhizosphere, leading to an increase in the population of N-fixing bacteria [50,51].…”
Section: Discussionsupporting
confidence: 87%
“…They play a crucial role in enhancing plant growth through various mechanisms. They facilitate phosphorus dissolution, nitrogen fixation and an improved mineral uptake, thereby promoting efficient nutrient utilization and enhancing both shoot and root development [28,38,46]. Additionally, PGPR can enhance a plant's resistance to diseases and abiotic stresses by influencing plant secondary metabolism, detoxifying heavy metals, regulating ethylene levels and emitting volatile organic compounds [47,48].…”
Section: Effects Of Biofertilizers On Plant Growth Parametersmentioning
confidence: 99%
“…These environmentally friendly fertilizers also contribute to reducing carbon emissions in the environment. The practical application of rhizobacterial processes, such as biofertilization, phyto-remediation and cross-protection, depends on the ability to produce desired strains and the existing population of microorganisms [28]. Many rhizobacteria benefit plant growth and enhance plant tolerance to biotic and abiotic stresses [29,30].…”
Section: Introductionmentioning
confidence: 99%